Reporting and methodological quality of systematic literature reviews evaluating the associations between e-cigarette use and cigarette smoking behaviors: a systematic quality review - Mimi M. Kim (BMC, 2021)
Abstract Introduction Several published systematic reviews have examined the potential associations between e-cigarette use and cigarette smoking, but their methodological and/or reporting quality have not yet been assessed. This systematic quality review followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and AMSTAR (A MeaSurement Tool to Assess systematic Reviews) 2 to evaluate the quality of systematic reviews investigating potential associations between e-cigarette use and cigarette smoking. Materials and methods PubMed/MEDLINE, Embase, and PsycINFO were searched from 01 January 2007 to 24 June 2020. Methodological quality was assessed using AMSTAR 2, and reporting quality was assessed using PRISMA guidelines. Results Of 331 potentially relevant systematic reviews, 20 met predefined inclusion criteria. Most reviews (n = 15; 75%) reported on e-cigarette use and cigarette smoking cessation, while three reported on e-cigarette use and cigarette smoking initiation (15%); and two reported on cigarette smoking initiation and cessation (10%). According to AMSTAR 2 guidelines, 18 of the 20 reviews (90%) were “critically low” in overall confidence of the results, while two were ranked “low.” Additionally, reporting quality varied across the reviews, with only 60% reporting at least half of the PRISMA items. Discussion Methodological limitations were identified across reviews examining potential associations between e-cigarette use and cigarette smoking behaviors, indicating that findings from these reviews should be interpreted with caution. Conclusions Future systematic reviews in this field should strive to adhere to AMSTAR 2 and PRISMA guidelines, to provide high quality syntheses of the available data with transparent and complete reporting.